City of heavenly fire - Clare, Cassandra 1973- (The mortal instruments, 2014)
"Darkness has descended on the Shadowhunter world. Chaos and destruction overwhelm the Nephilim as Clary, Jace, Simon, and their friends band together to fight the greatest evil they have ever faced: Clary's own brother. Nothing in this world can defeat Sebastian...but if they journey to the realm of demons, they just might have a chance.."..